2014
DOI: 10.1120/jacmp.v15i4.4737
|View full text |Cite
|
Sign up to set email alerts
|

Frameless stereotactic body radiation therapy for multiple lung metastases

Abstract: Two patients with multiple lung metastases (≥ 5) were treated using frameless stereotactic body radiation therapy (SBRT) on an Elekta Axesse linear accelerator equipped with an interdigitation‐capable multileaf collimator and four‐dimensional cone‐beam CT (4D CBCT). The technique and the early clinical outcomes were evaluated. Patient A with five lung metastases and Patient B with seven lung metastases underwent SBRT (48 Gy/8 fractions for Patient A, 42 Gy/7 fractions for Patient B). The treatments were admini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 23 publications
0
24
0
Order By: Relevance
“…However, elderly patients who developed multiple primary or oligometastases (<5 lesions) lung lesions with associated co‐morbidities may not retain their treatment position for traditional long SBRT treatment times with an individual isocenter placed for each lesion. Treating multiple lung lesions synchronously with a single‐isocenter plan, either using intensity‐modulated radiation therapy (IMRT) or volumetric arc therapy (VMAT), has been studied by a few researchers . Furthermore, utilizing flattening filter free (FFF) beam for single‐isocenter multiple‐lesion VMAT lung stereotactic body radiation therapy (SBRT) treatment was fast and efficient, improved the patient comfort and is gaining popularity in clinical practice …”
Section: Introductionmentioning
confidence: 99%
“…However, elderly patients who developed multiple primary or oligometastases (<5 lesions) lung lesions with associated co‐morbidities may not retain their treatment position for traditional long SBRT treatment times with an individual isocenter placed for each lesion. Treating multiple lung lesions synchronously with a single‐isocenter plan, either using intensity‐modulated radiation therapy (IMRT) or volumetric arc therapy (VMAT), has been studied by a few researchers . Furthermore, utilizing flattening filter free (FFF) beam for single‐isocenter multiple‐lesion VMAT lung stereotactic body radiation therapy (SBRT) treatment was fast and efficient, improved the patient comfort and is gaining popularity in clinical practice …”
Section: Introductionmentioning
confidence: 99%
“…A sliding scale is then used to find the best ‘compromise’ match between the two surrogates. Successful application of this software has been reported for patients receiving radiotherapy for lung cancer and regional lymph nodes, multiple lung metastases and for post‐prostatectomy surgical bed …”
Section: Discussionmentioning
confidence: 99%
“…A sliding scale is then used to find the best 'compromise' match between the two surrogates. Successful application of this software has been reported for patients receiving radiotherapy for lung cancer and regional lymph nodes, 36 multiple lung metastases 37 and for post-prostatectomy surgical bed. 38 In conclusion, for disease sites that require the concurrent irradiation of multiple, independently moving CTVs, there is a complex geometric interplay between the magnitude of CTV displacement differences, the PTV margins and the image guidance strategy applied.…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, our research group has reported the ability of 4D‐CBCT to acquire highly accurate images from a respiratory motion phantom . Several studies have reported that 4D‐CBCT can be used to manage respiratory motion in clinical cases . They stated that 4D‐CBCT can observe the internal margin and the motion of a tumor during treatment with high accuracy, and that 4D‐CBCT can be used for stereotactic body radiotherapy as an IGRT device.…”
Section: Introductionmentioning
confidence: 93%